A COMPARATIVE STUDY ON ISOMETRIC STRENGTH BETWEEN JUDOKAS AND WEIGHTLIFTERS. - S, Shashi kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study focuses on comparing the isometric strength between Judokas and weightlifters. Isometric strength, which refers to the maximum force a muscle can produce without varying its length, is a key aspect in both sports, albeit manifested differently. Weightlifting emphasizes maximum strength and explosive power in control, whereas Judo requires a combination of strength, endurance, and dynamic control across unpredictable movements. To achieve the aim of the present study, 20 male weightlifters and 20 male Judokas, a total of 40 athletes, were selected randomly as subjects of Karnataka State. The researcher selected the hand grip dynamometer test to evaluate the isometric strength of the subjects, and descriptive statistics and two-sample t-tests were used to analyse the data. The findings revealed a significant difference between Judokas and weightlifters. It has been concluded that weightlifters have a stronger isometric strength than the Judokas in state of Karnataka.